2013
DOI: 10.1155/2013/608797
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Petroleum-Based Fuel from Waste Plastics and Performance Analysis in a CI Engine

Abstract: The present work involves the synthesis of a petroleum-based fuel by the catalytic pyrolysis of waste plastics. Catalytic pyrolysis involves the degradation of the polymeric materials by heating them in the absence of oxygen and in the presence of a catalyst. In the present study different oil samples are produced using different catalysts under different reaction conditions from waste plastics. The synthesized oil samples are subjected to a parametric study based on the oil yield, selectivity of the oil, fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 7 publications
2
37
0
Order By: Relevance
“…The mechanical efficiency increased with the increase of brake power for WPO and diesel blends; NOx emissions were decreased with the increase of CO emission by increasing engine load. Unburnt HC decreased with the increase of WPO blends . Above 75 volume percentage blends of WPO with diesel reduced the performance characteristics such as torque and power by 23.79% when specific fuel consumption was increased about 31.22% with reduced thermal efficiency up to 5.97% compared with diesel operations .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The mechanical efficiency increased with the increase of brake power for WPO and diesel blends; NOx emissions were decreased with the increase of CO emission by increasing engine load. Unburnt HC decreased with the increase of WPO blends . Above 75 volume percentage blends of WPO with diesel reduced the performance characteristics such as torque and power by 23.79% when specific fuel consumption was increased about 31.22% with reduced thermal efficiency up to 5.97% compared with diesel operations .…”
Section: Introductionmentioning
confidence: 93%
“…Also, the increased concentration of WPO in diesel led to decreased BTE because of higher fuel consumption. Some studies reported that lower BTE was pointed with pure WPO on the diesel engine because of higher viscosity .…”
Section: Utilization Of Waste Plastic Oil With Diesel Enginementioning
confidence: 99%
“…Plastics are used in many applications (Bashir, 2013) because of their versatility, light weight and also easy to manufacture (Andrady & Neal, 2009). Plastics are used extensively in automobiles (Gerrard & Kandlikar, 2007;Mazzanti & Zoboli, 2006;Smink, 2007), building and constructions (Cleetus, Thomas, & Varghese, 2013), packaging (Al-Salem, Lettieri, & Baeyens, 2009), bags (Bashir, 2013) and phones (Kasper et al, 2011;Yamane, de Moraes, Espinosa, & Tenório, 2011) and computers (Balakrishnan, Anand, & Chiya, 2007;Guo, Guo, & Xu, 2009;Hall & Williams, 2007). As a consequence, the production of plastics has increased substantially over the last 60 years .…”
Section: The Waste Plastic Situationmentioning
confidence: 99%
“…Fuel oil from waste plastics has a high heating value (Cleetus et al, 2013;Kumar & Singh, 2013 Vol. 10, No.…”
Section: Potential Application Of the Estimated Amount Of Fuel Oil Frmentioning
confidence: 99%
“…Nature of the liqor from pyrolytic process depends on its raw material, such as to produce fuel the raw material comes from plastic waste 11 .The ingredients of wood vinegar also depend on the temperature of the pyrolysis process. Materials such as coal, animal and human waste, food scraps, agriculture waste, paper, hardwood, cardboard, plastics, rubber, and biomass are suitable for pyrolysis 12 .…”
Section: Introductionmentioning
confidence: 99%